Efficacy of antiviral drug AV2 in the treatment of human papillomavirus-associated precancerous lesions of the uterine cervix: A randomized placebo-controlled clinical trial in Kinshasa, DR Congo. (KINVAV study) - Mutombo, Alex Baleka (Contemp Clin Trials Commun, 2017)
BACKGROUND: Cervical Cancer (CC) is a major public health problem in DR Congo; the high incidence of CC is due to the inexistence of effective screening programs based on cytology and/or HPV detection followed by appropriate treatments. This situation highlights the need to implement efficacious and inexpensive treatment methods. This study aims at evaluating the efficacy of a topical antiviral drug named AV2(®) as a treatment for HPV-associated lesions of the cervix. METHODS: Women will undergo cytology sampling, HPV testing and Visual inspection of the cervix after application of 5% acetic acid (VIA). VIA-positive women will be randomized to one of two groups to receive treatment by either AV2(®)or placebo. They will undergo control examinations after two months and after six months. In case of persistent lesions on VIA, treatment by cryotherapy will be done. The primary outcomes will be the change of lesions, the clearance of HPV DNA, and the correlation of the two 2 months after treatment with AV2(®). CONCLUSION: This study is the first large-scale study in Africa to evaluate systematically the efficacy and safety of a topical antiviral drug for the treatment of HPV— associated lesions of the cervix. Its findings will direct the planning of suitable algorithms for CC screening and treatment. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov – Unique identifier: NCT02346227, registered on November 8, 2014.